2013
DOI: 10.1007/s13244-013-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical ultrasound features of parathyroid tumours may bear a relationship to their clinical and biochemical presentation

Abstract: ObjectivesTo describe atypical ultrasound features of parathyroid lesions and correlate them with clinical presentation and histopathology.Materials and methodsRetrospective review of 264 patients with primary hyperparathyroidism who underwent ultrasound imaging prior to parathyroidectomy was performed. Patients with atypical ultrasound findings (n = 26) were identified; imaging findings were correlated with clinical presentation and histopathology.ResultsTwenty-one (80 %) lesions were adenomas, two (8 %) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…There are scarce data in the literature concerning the prevalence and relevance of atypical ultrasound features for the evaluation of parathyroid lesions. Our study supports a previous report, which suggested that parathyroid lesions with atypical imaging features are associated with a higher incidence of malignancy (25). Moreover, in our study, the AUC for the longest adenoma diameter measured by ultrasonography was statistically significant, and the best cut-off value for predicting aggressive disease was 21.5 mm.…”
Section: Discussionsupporting
confidence: 91%
“…There are scarce data in the literature concerning the prevalence and relevance of atypical ultrasound features for the evaluation of parathyroid lesions. Our study supports a previous report, which suggested that parathyroid lesions with atypical imaging features are associated with a higher incidence of malignancy (25). Moreover, in our study, the AUC for the longest adenoma diameter measured by ultrasonography was statistically significant, and the best cut-off value for predicting aggressive disease was 21.5 mm.…”
Section: Discussionsupporting
confidence: 91%
“…Chandramohan et al analyzed atypical US features of 26 parathyroid lesions. According to their study the ratio of non-hypoechoic PAs reaches up to 27% due to haemorrhage, hyalinisation and fibrosis in adenomatous tissue [22]. In the presented series, 9% of the PAs were hyperor isoechoic relative to the echogenicity of thyroid gland.…”
Section: Discussionmentioning
confidence: 62%
“…In most consecutive series of patients undergoing surgery for PHPT, the incidence of atypical parathyroid adenoma ranged from 0.5 to 4.4% (de Meneses Montenegro et al 2006, Ippolito et al 2007, Juhlin et al 2010, O'Neal et al 2011, Ricci et al 2012, Chandramohan et al 2014, Haglund et al 2015, McCoy et al 2015, Quinn et al 2015, Schneider et al 2015, Ozolins et al 2016, Mamedova et al 2017. An incidence as high as 14% has been reported in the Asian countries (Cakir et al 2016, Hu et al 2018.…”
Section: Epidemiologymentioning
confidence: 99%